IMPLEMENTASI MANAJEMEN PENDIDIKAN KARAKTER DALAM MENGEMBANGKAN MINAT,SIKAP,DAN PRILAKU POSITIF SISWA - Suprapto, Ahmad Rofi’i,Yuli Habibatul Imammah (UNISAN JURNAL, 2024)
The aim of this research is to determine 1) Implementation of Character Education Management in developing students’ positive behavior 2) Obstacles encountered in developing students’ positive behavior through character education 3) Efforts to overcome obstacles to developing students’ positive behavior. The research method of this research is qualitative research. Data collection techniques in this research are interviews, observation, documentation, and/or a combination of several techniques. Data sources are Field Literature, Field Research. Based on the research results, the implementation of character education management in developing students’ positive interests, attitudes and behavior is competency in preparing learning plans, competency in describing the curriculum, competency in conducting evaluations. Obstacles in developing students’ interests, attitudes and positive behavior are: Low interest in madrasas, Lack of learning resources, Low learning motivation of students, Lack of religious facilities. Facilities such as prayer rooms for prayer practice, Arabic language and recitation laboratories, as well as software are still limited. Efforts made to overcome obstacles to developing students’ interests, attitudes and positive behavior are: Intensifying the discipline of madrasah residents, Providing learning facilities and infrastructure , Arouse student interest using various methods. Teachers carry out evaluations not only cognitively but also psychomotor and affectively, so that character education can develop students’ positive interests, attitudes and behavior well. Keywords: Management, character education, positive behavior